Younger Dryas ice margin retreat in Greenland: new evidence from southwestern Greenland - Funder, Svend; Sørensen, Anita H. L.; Larsen, Nicolaj K.; Bjørk, Anders A.; Briner, Jason P.; Olsen, Jesper; Schomacker, Anders; Levy, Laura B.; Kjær, Kurt H. (Climate of the Past, 2021)
To date the final stage in deglaciation of the Greenland shelf, when a contiguous ice sheet margin on the inner shelf transitioned to outlet glaciers in troughs with intervening ice-free areas, we generated cosmogenic 10 Be dates from bedrock knobs on six outlying islands along a stretch of 300 km of the southwestern Greenland coast. Despite 10 Be inheritance influencing some dates, the ages generally support a Greenland Ice Sheet (GrIS) margin that retreated off the inner shelf during the middle Younger Dryas (YD) period. Published 10 Be- and 14 C-dated records show that this history of the GrIS margin is seen in other parts of Greenland but with large variations in the extent and speed of retreat, sometimes even between neighbouring areas. Areas with a chronology extending into the Allerød period show no marked ice margin change at the Allerød–YD transition except in northernmost Greenland. In contrast, landforms on the shelf (moraines and grounding zone wedges) have been suggested to indicate YD readvances or long-lasting ice margin stillstands on the middle shelf. However, these features have been dated primarily by correlation with cold periods in the ice core temperature records. Ice margin retreat during the middle and late YD is explained by advection of warm subsurface water at the ice margin and by increased seasonality. Our results therefore point to the complexity of the climate–ice margin relation and to the urgent need for direct dating of the early deglaciation history of Greenland.